Immunohistochemical features of progesterone receptors expression of placental barrier in women with multiple pregnancies resulting from assisted reproduction - T. D. Zadorozhna; B. M . Ventskivsky; S. M. Kylyhevich; I. V. Poladich (Patologìâ)
Hormonal disorders are one of the main known causes of miscarriage and preterm birth in multiple pregnancies resulting from assisted reproductive technology (ART). Progesterone and the number of its receptors play an important role in the preservation and prolongation of pregnancy and it is the pressing issue of our time. The study of placentas, as the main site of synthesis of progesterone, has high informative potential and it is the most important diagnostic object, and information received by its research is essential for the full conclusion on the causes, mechanisms, close and long-term effects of multiple pregnancy pathology.